Impact of localization phenomenon and temperature on the photoluminescence spectra of GaSbBi alloys and GaSbBi/GaAs quantum dots. (May 2019) - Hidouri, T.; Mal, I.; Samajdar, D.P.; Saidi, F.; Das, T.D.
Abstract: In this work, the low temperature PL spectrum of GaSbBi ternary alloys and GaSbBi/GaAs Quantum Dots (QDs) are investigated using two different mathematical models. The first model based on the Gaussian distribution of the localized states takes into consideration the carrier dynamics associated with bulk and QD systems through the inclusion of different carrier dependent parameters such as carrier generation rate, recapture, thermal escape, radiative and non-radiative recombination times and localization depth to compute and reproduce the temperature dependent of the luminescence keys. Thek dot p method realized using a 10 band Hamiltonian is used to calculate the carrier effective masses from the temperature dependent band diagram which serves as an input to reproduce the PL spectra. Two separate expressions of intrinsic carrier concentration for bulk and QD used in this model help to achieve a close agreement between the theoretically calculated results and experimental data. This work imparts a deep level understanding of the behaviour of carriers and optoelectronic parameters in III-V-Bi structures. Highlights: Effect of temperature on PL spectra of GaSbBi and GaSbBi/GaAs QDs is studied. Anomalous S shaped variation of PL peak energy for GaSbBi/GaAs QDs is explained by LSE Model. k dot p method is used to successfully reproduce the temperature dependent PL spectra. The optoelectronic properties of GaSbBi alloys and QDs are investigated using mathematical models.